The effect of weaving and non-weaving multi-pass procedure on microstructure and mechanical properties in GMAW of S960QL - Mert, Tolga; Gurol, Ugur; Tumer, Mustafa (SPRINGER LONDON LTD, 2023)
Microstructural transformations and mechanical properties of weld metals obtained by gas metal arc welding (GMAW) of S960QL quenched and tempered ultra-high-strength steels (UHSS) with 15 mm thickness were investigated. Welded joints were acquired by using undermatching filler metal. Selected weaving and non-weaving multi-pass procedures have influenced weld metal heat inputs and number of passes. Mechanical properties of the weld metals were characterized by Charpy, hardness, and tensile tests, and these results were correlated with microstructural characterizations using an optical microscope and scanning electron microscope. Acicular ferrite is predominant in both of the weld metals, and microstructure of the weld metal obtained by weaving multi-pass has coarser grain structure. Fine lath martensite formation in non-weaving joint's weld metal with low heat input was more intense than weaving joint's weld metal with high heat input. Lath martensite acquired due to rapid cooling in non-weaving joint's weld metal provided adequate strength properties. Although toughness values were low, they have met relevant standard requirements.
Keywords: Ultra-high-strength steel; Gas metal arc welding; Weaving and non-weaving pass; Toughness; Lath martensite; Acicular ferrite; WELD METAL; IMPACT TOUGHNESS; HEAT-TREATMENT; STEEL; STRENGTH; TEMPERATURE; Automation & Control Systems; Engineering